Pengaruh Perputaran Kas, Perputaran Piutang Dan Perputaran Persediaan Terhadap Profitabilitas Pada Perusahaan Farmasi - Zahra, Firlia Adnina; Nasution, Raden (Fakultas Ekonomi dan Bisnis Universitas Ibn Khaldun Bogor, 2022)
This study intends to determine and to some extent dissect the effect of cash turnover, accounts receivable turnover and inventory turnover on profitability. To determine the concurrent effect of cash turnover, accounts receivable turnover and inventory turnover on profitability. In this review, the technique used is a quantitative strategy with a sample of 45 pharmaceutical companies used. Examination of the information used is a direct relapse examination which is different by using partial and simultaneous tests. The results of this study are that the cash turnover variabel does not significantly affect profitability, the accounts receivable turnover variabel has an influence on profitability. Inventory turnover variabels affect profitability Taken together, cash turnover, accounts receivable turnover and inventory turnover affect the p